Implementation Of Message Security In Pictures Using Playfair Chiper Algorithm: Implementation Of Message Security In Pictures Using Playfair Chiper Algorithm - Muhamad Maksum Hidayat; Wahyu Nugroho; Dony Ariyus (Institute of Computer Science (IOCS), 2020)
Cryptography implementations are now widely solved by cryptanalyst in the process of securing a messaging system, and therefore the need to add a method of steganography. Steganography is the art of hiding secret messages in any medium other than the sender and receiver that no one would know or realize there is a secret message in the media is sent. In this journal, conducted a study on the implementation of cryptography in the form of encryption and decryption of a message using the Playfair cipher algorithm is modified by letter hijaiyah. Then the implementation of steganography in a PNG image media, the testing process is done by sending the media image using email, whatsapp, facebook, and telegram. research aims to make the encryption process stronger and more secure,